Klasifikasi Kisaran Harga Tarif Endorsement Influencer Instagram dengan Metode Decision Tree - Jeshen Oktavian Nathanel; Alexander Setiawan (Jurnal Infra, 2022)
Digital marketing in this era of globalization is mandatory for small business owners or businesses that have developed. Marketing using Instagram Influencers is one way. Oftentimes, influencers set their prices according to the followers they have, while not necessarily posting can engage their followers who are active and not fake. The problem that researchers want to solve is the classification of endorsement prices according to the data they have by looking at other than followers such as engagement rate, average liker, and average comment so that the prices set by influencers are more in line with the data they have. The method used for classification is Decision Tree with CART algorithm. The resulting model will be used to classify influencer endorsement prices. The results from testing the model used are only able to achieve 50% accuracy with a RMSE value of 1.12 to classify influencer endorsement prices.